Sexual harassment or disinhibition? Residential care staff responses to older adults' unwanted behaviours. (28th October 2021) - Cook, Catherine M.; Schouten, Vanessa; Henrickson, Mark; McDonald, Sandra; Atefi, Narges
Abstract: Background: The ethical complexity of residential care is especially apparent for staff responding to residents' inappropriate sexual expression, particularly when directed towards care workers as these residents are typically frail, often cognitively impaired, and require ongoing care. Objectives: To explore staff accounts of how they made meaning of and responded to residents' unwanted sexual behaviours directed towards staff. This exploration includes whether staff appeared to accept harassment as a workplace hazard to be managed, or an unacceptable workplace violation, or something else. Methods: These qualitative data are drawn from a national two‐arm mixed method study in Aotearoa New Zealand undertaken in 35 residential care facilities. Semi‐structured interviews were conducted with 77 staff, residents and family members. Interpretive description was used to analyse the data. Results: Staff had numerous ways they used to respond to behaviours: (1) minimisation, deflection and de‐escalation, where staff used strategies to minimise behaviours without requiring any accountability from residents; (2) holding residents accountable, where staff to some degree addressed the behaviour directly with residents; (3) blurred boundaries and complexities in intimate long‐term care, where staff noted that in a context where touch is common‐place, cognitive function was diminished and relationships were long‐term, boundaries were easily breached; (4) dehumanising and infantilising residents' behaviours, where staff appeared to assert control through diminishing the residents' identity as an older person. It was evident that staff had developed considerable practice wisdom focused on preserving the care relationship although few referred to policy and education guiding practice. Conclusions: Staff appeared to be navigating a complex ethical terrain with thoughtfulness and skill. Care workers seemed reluctant to label resident behaviour as sexual harassment, and the term may not fit for staff where they perceive residents are frail and cognitively impaired. Implications for practice: Policy, education and clinical leadership are recommended to augment practice wisdom and ensure staff and resident safety and dignity and to determine how best to intervene with residents' unwanted sexual behaviours.